Matching individual patient needs and desires throughout end of life stages. Issue 1 (March 2014) - James, June
Abstract: End of life care is a subject that many patients or health care professionals would prefer not to talk about. People with diabetes have a unique set of care needs during the last year, months and days of life, but until now there has been little guidance on their specific clinical requirements. Approximately half a million people die in England each year and around 75 000 of them will have diabetes. European statistics demonstrate important variations in mortality and the burden of disease related to diabetes with age standardised death rates per 100 000 ranging from 4.0 (Greece) to 17.9 (Portugal), and with higher levels ranging from 36.1 (Israel) to 46.8 (Armenia). It is important that health care professionals are equipped with the knowledge, skills and clear guidance in order to support patients, relatives and carers during what is often a difficult time for all. This article gives a robust definition of the term 'end of life', discusses the demise of more generic United Kingdom guidance on the care of the dying, and presents a consensus approach to quality care for people who are nearing the end of their life. These recommendations were commissioned by Diabetes UK, developed by a multidisciplinary group of heath care professionals and endorsed by key diabetes organisations. The recommendations given can easily be adopted for use in other countries, and the documents and tools are freely available to all.